2009
DOI: 10.1889/1.3256758
|View full text |Cite
|
Sign up to set email alerts
|

20.1: Perceived Brightness of LED Projector

Abstract: It is commonly observed that the LED projectors can provide with more perceived brightness by less stimulus luminance. In this work, the Helmholtz‐Kohlrausch effect is applied for studying the enhanced perceived brightness of the LED projector. According to the equations developed by Nayatani's group, the ratio of the enhanced perceived brightness of LED projector is evaluated as 25% to 30% as compared to traditional lamp projector in dark environment. However, in the normal office illumination level, the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…For related colors, Nayatani et al reported that the H‐K effect is changed by the chroma and hue of a color stimulus, for example, the H‐K effect of high chroma is larger than that of low chroma and the H‐K effect of red is larger than that of green, and also proposed using the prediction equations of the variable achromatic color (VAC) method and the variable chromatic color (VCC) method as equations for calculating the magnitude of the H‐K effect . Liao et al showed by using the prediction equation created by Nayatani's group that the perceived brightness of an LED projector is higher than that of a lamp projector, which has narrower gamut than an LED projector even if the two projectors have the same white point and luminance . In addition to these prediction equations, the prediction equation of the CIE200, which takes account of the H‐K effect and the Purkinje effect, has also been proposed .…”
Section: Introductionmentioning
confidence: 99%
“…For related colors, Nayatani et al reported that the H‐K effect is changed by the chroma and hue of a color stimulus, for example, the H‐K effect of high chroma is larger than that of low chroma and the H‐K effect of red is larger than that of green, and also proposed using the prediction equations of the variable achromatic color (VAC) method and the variable chromatic color (VCC) method as equations for calculating the magnitude of the H‐K effect . Liao et al showed by using the prediction equation created by Nayatani's group that the perceived brightness of an LED projector is higher than that of a lamp projector, which has narrower gamut than an LED projector even if the two projectors have the same white point and luminance . In addition to these prediction equations, the prediction equation of the CIE200, which takes account of the H‐K effect and the Purkinje effect, has also been proposed .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the practical applications, any projecting secondary color by mixing from various combination of three primaries. The additivity among the estimated B/L ratios of the RGB primaries becomes an essential issue to be verified [14]. Several secondary color stimuli mixed by the RGB primaries has been checked for their perceived brightness and compared with the estimated ones by the addition of the B/L ratios of each R, G, or B primaries according to their color mixing ratios.…”
Section: Methodsmentioning
confidence: 99%
“…In real-world use cases this brightness benefit can be significant, even compared to the latest generation of wide-gamut LCDs. If we consider the chromaticity coordinates of a DMS display compared to a generic display working in sRGB gamut, as shown in Table 1 below, then we find that the perceived brightness gain (as derived using the methods in [16][17], for example) as a function of ambient illuminance L a , and for a display luminance of 400 cd/m 2 , is as per Figure 3. The perceived brightness gain associated with a wide gamut display can therefore approach 25%, even in an office environment.…”
Section: Impactmentioning
confidence: 97%